Structural Optimization Simulation of MHPA-PV/T Module for Xizang - Wan, Li (Scientific Journal of Technology, 2025)
This article establishes a mathematical model for the operation of MHPA-PVT system and uses Fluent simulation software to build a three-dimensional steady-state model of MHPA-PVT components. Based on the verification of the reliability of the model, optimization research is conducted on the laying, arrangement direction, and condensation section length of the micro heat pipe array. Taking into account the cost, benefits during use, and service life, the component is still the most suitable for a fully deployed micro heat pipe array; The arrangement directions of different micro heat pipe arrays (horizontal and vertical) have little difference in the thermal and electrical performance of the components; The increase in the length of the condensation section can improve the power generation efficiency, but it will reduce the heat collection efficiency.